2021
DOI: 10.1001/jamapsychiatry.2020.4402
|View full text |Cite
|
Sign up to set email alerts
|

Trends in US Emergency Department Visits for Mental Health, Overdose, and Violence Outcomes Before and During the COVID-19 Pandemic

Abstract: IMPORTANCEThe coronavirus disease 2019 (COVID-19) pandemic, associated mitigation measures, and social and economic impacts may affect mental health, suicidal behavior, substance use, and violence.OBJECTIVE To examine changes in US emergency department (ED) visits for mental health conditions (MHCs), suicide attempts (SAs), overdose (OD), and violence outcomes during the COVID-19 pandemic. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study used data from the Centers for Disease Control and Prevention'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
453
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(501 citation statements)
references
References 25 publications
41
453
5
2
Order By: Relevance
“…Overall, there is accumulating evidence on the negative consequences of the COVID-19 pandemic on public mental health. A number of cross-sectional and longitudinal cohort studies have found detrimental effects of the pandemic on various mental health domains, including psychological distress, depression, anxiety, and an increase of more distal risk factors such as cannabis and alcohol misuse and loneliness [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These findings are largely in line with findings from this nationally representative survey, i.e., high levels of social isolation, lack of company, COVID-19-related worrying, and anxiety have been reported and found to impact psychological distress in youth during active lockdown in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is accumulating evidence on the negative consequences of the COVID-19 pandemic on public mental health. A number of cross-sectional and longitudinal cohort studies have found detrimental effects of the pandemic on various mental health domains, including psychological distress, depression, anxiety, and an increase of more distal risk factors such as cannabis and alcohol misuse and loneliness [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These findings are largely in line with findings from this nationally representative survey, i.e., high levels of social isolation, lack of company, COVID-19-related worrying, and anxiety have been reported and found to impact psychological distress in youth during active lockdown in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 may influence the methods in which individuals use substances and their risk for fatal and nonfatal overdoses. When contrasting median emergency department rates from 2019 and 2020, data from the Centers for Disease Control and Prevention's National Syndromic Surveillance Program revealed a significant increase in overdoses for opioids and for all substances in 2020 compared with 2019 [ 15 ▪ ]. Additionally, National Emergency Medical Services Information System (NEMSIS) data found that rates of overdose-related cardiac arrests per emergency medical services activations were elevated in 2020 compared with 2019 and 2018 [ 16 ▪▪ ].…”
Section: Overdose Riskmentioning
confidence: 99%
“…The opioid and COVID-19 epidemics have collectively precipitated an increase in opioid-related mortality in 2020 [ 1 ]. More than 3500 Emergency Departments (ED) in the United States reported that opioid overdoses consistently increased in 2020 compared to 2019 [ 2 ]. Prior to COVID-19, strict state and federal regulations and laws (in the United States) such as The Ryan Haight Act of 2008, the Drug Addiction Treatment Act of 2000, and 42 CFR 8 for opioid treatment programs (OTPs) enforced by the Substance Abuse and Mental Health Service Administration and Drug Enforcement Agency made opioid treatment difficult, time consuming, and costly for patients to access and receive medication and care.…”
Section: Introductionmentioning
confidence: 99%